Analisis Penerapan Aplikasi Si Apik untuk Membantu Penyusunan Laporan Keuangan Berdasarkan SAK EMKM - Maulidah, Hikmatul; Krisdiyawati, Krisdiyawati (AKUNSIKA: Jurnal Akuntansi dan Keuangan, 2024)
This study aims to apply the Android-based accounting application Si Apik in assisting MSMEs in compiling financial reports in accordance with SAK EMKM. The application of an android-based accounting application is very important because it can present reliable information effectively and efficiently so as to facilitate operational activities to decision making. This type of research is descriptive research with a qualitative approach. The types of data that will be used in this study are qualitative data and quantitative data. This study uses data collection techniques with interviews, observation, and documentation. The data analysis technique in this study was carried out by implementing the Si Apik android application at the company for 1 month followed by analyzing the output produced by the Si Apik application. Based on the research results, the Si Apik application can be used easily and practically. With the Si Apik application, it makes it easier for MSMEs to make financial reports because this application automatically creates financial reports based on SAK EMKM